Implementation of Internal Communication of PT. Meteor Sriwijaya Mandiri Palembang in an Effort to Maintain Employee Loyalty - Maya Agustina Fyranti; Henny Yusalia; Gita Astrid (Universitas Muhammadiyah Palu, 2025)
This study aims to examine the implementation of internal communication at PT. Meteor Sriwijaya Mandiri Palembang in an effort to maintain employee loyalty. Newly established and logistics companies face challenges such as occupational safety risks and potential turnover, so effective internal communication is key in building harmonious relationships and increasing employee commitment. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Common systems theory is used to look at how the reciprocal relationships between parts within an organization play a role in achieving common goals. The theory used in this study is the general systems theory of Ludwig von Bertalanffy, which emphasizes the importance of reciprocal relationships between sub-systems in achieving common goals. The results of the study show that the implementation of internal communication at PT. Meteor Sriwijaya Mandiri Palembang is quite effective, although there are some obstacles in communication that need to be fixed. Also, in an effort for employees to show loyalty through discipline and responsibility, while the company creates a work environment that supports and fulfills employee rights.